THE USE OF DEIXIS IN GLADIATOR MOVIE MANUSCRIPT - Hasanah, Chuswatul; Laila, Malikatul; Prasetyarini, Aryati (Kajian Linguistik dan Sastra, 2006)
This study is about the forms and references of deixis udes in "Gladiator" movie manuscript. The data, movie discourse are taken from observation and documentation using techniques of reading, indentifying, and noting. The data source is "Gladiator" movie manuscript. To identify the forms of deixis, the writer udes the theory of deixis in Discourse Analysis while to clarifying the references of deixis, the writer used the theory of meaning focusing on both semantic and pragmatic meaning. The result of study shows that the forms of deixis are person deixis, place dixis, time deixis, discourse deixis, and social deixis. Person dixis consists of first person, second person, and thrid person singular and plural. It is also distinguished based on its function in the sentence as subject and object personal pronoun, subject in possesive personal pronoun, object ini possesive personal pronoun and reflexive personal pronoun. The reference of deixis bades on semantic meaning refers to lexical meaning while based on pragmatic meaning refers to the meaning covered in the discourse, such as referring to the interlocutors, the war, the time process during the war, and the social relationship among the participants in the war.Â Key words:Â deixis, deictic, proximal, and distal